Factors Affecting the Decision to Use the GHB ALL GEN Application Among Government Housing Bank Customers, Nakhon Ratchasima Province - Saengwannakul, Busakorn; Phatanarajata, Lilawadi (MBA-KKU Journal, 2025)
The objectives of this study are: (1) to examine the factors influencing the decision-making process in choosing the GHB ALL GEN application, (2) to assess the level of technology acceptance affecting the decision-making process in choosing the GHB ALL GEN application, and (3) to study the level of service quality that affects the decision to use the GHB ALL GEN application among Government Housing Bank customers in Nakhon Ratchasima Province. The sample consisted of 400 users of the GHB ALL GEN application, selected from Government Housing Bank customers in Nakhon Ratchasima province. Data were collected using a questionnaire and analyzed using frequency, percentage, mean, standard deviation, t-test, one-way ANOVA, and Pearson’s correlation coefficient. The results revealed that gender, age, education level, and occupation significantly influenced the decision to use the application (p < 0.05), while marital status and average monthly income did not show significant differences. Furthermore, both technology acceptance and service quality were found to have a strong positive correlation with the decision to use the GHB ALL GEN application, with statistical significance at the 0.01 level